The dielectric properties of some ceramic substrate materials at terahertz frequencies. Issue 14 (November 2019) - Ma, Mingsheng; Wang, Yi; Navarro-Cía, Miguel; Liu, Feng; Zhang, Faqiang; Liu, Zhifu; Li, Yongxiang; Hanham, Stephen M.; Hao, Zhangcheng
Abstract: The terahertz (THz) dielectric constant ( ε r ' ) and dielectric loss tangent ( tan δ ) of the commercial LTCC materials (Ferro A6M and DuPont 951), Al2 O3 (ceramic and single crystal), AlN and β-Si3 N4 ceramics were measured using a vector network analyzer (VNA) over the frequency range of 140–220 GHz and a time-domain spectrometer (TDS) from 0.2 to 1.0 THz. The results from the two instruments are compared with the literature and show good agreement and consistency. For Ferro A6M, ε r ' = 6.06, tan δ = 0.012 at 1.0 THz. For DuPont 951, ε r ' = 7.67, tan δ = 0.097 at 1.0 THz. For Al2 O3 ceramic and single crystal, the measured THz dielectric properties are consistent with the reported works. The dielectric constant of AlN ( ε r ' = 8.85) and β-Si3 N4 ( ε r ' = 8.41) ceramics in the THz region is a little lower than those reported for the MHz to GHz region. These results provide valuable and much needed reference information for device designers and material scientists.